THE INFLUENCE OF USING INTEGRATED SCIENCE LEARNING MODULE WITH PROBLEM BASED LEARNING TOWARDS STUDENTS’ CRITICAL THINKING SKILL - Dwi Aprillia Setia Asih (RETEL Journal (Journal on Publication of The Research on Teaching and Language), 2015)
This research is aimed for investigate the influence of using integrated science module with Problem Based Learning (PBL) towards students’ critical thinking skill of class VIII. Experimental design used in this research was one group pretest-posttest design, which used three stages, namely: (1) giving test to measure the dependent variable before doing treatment, (2) giving experimental treatment to the subjects (variable X), and (3) giving another test to measure dependent variable after treatment. Data collection methods used in this research were test and questionnaire. Next, the data of students’ critical thinking skill was analyzed by using paired T-test and the data of students’ response was analyzed by using cut off score which was converted into quality category with scale 5 score guideline. According to the data analysis gained from the research: 1. the module gets students’ response during the process of teaching and learning which is scored from students’ response questionnaire that shows that module is good categorized, 2. There is an influence of using integrated science learning module with PBL towards students’ critical thinking skill of class VIII, and this statement is supported by the result of paired T-Test which is 0.001.